ANALISIS WACANA RUBRIK RESENSI PADA SURAT KABAR SOLOPOS EDISI JANUARI-DESEMBER 2017 SERTA RELEVANSINYA SEBAGAI BAHAN AJAR TEKS ULASAN DI SMP DAN SMA - Meilani Wahyu Pangestika; Ani Rakhmawati; Raheni Suhita (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
This research aimed at describing and explaining about (1) the discourse structure of review text on book review columns in Solopos Newspaper January-December 2017 edition; (2) the textual aspects of book review; (3) the contextual aspects of book review; (4) the relevance of book review columns in Solopos Newspaper January-December 2017 edition as the teaching materials of review text in Secondary Junior High Schools and in Secondary Senior High Schools. The type of this research is qualitative descriptive. The results of this research indicated that (1) the discourse structure of review text on book review columns included opening paragraph, contacting paragraph or content, and closing paragraph; (2) textual aspects supporting the completeness of book review were the topic of discourse, aspects of cohesion and coherence, and forms of words; (3) the contextual aspects on book review could be understood through four interpretive principles, namely: the principle of personal interpretation, the principle of local interpretation, the principle of temporal interpretation, and the principle of analogy; and (4) the results of this research also indicated that book review columns in Solopos Newspaper January-December 2017 edition could be used as the teaching materials of review text in Junior High Schools and Senior High Schools.